Pengaruh Media Pembelajaran Interaktif Terhadap Hasil Belajar Siswa Dalam Pembelajaran Bimbingan Teknologi Informasi dan Komunikasi Kelas X di SMAN 1 Tigo Nagari - Afnila, Yolni Gusnanda; Khairuddin, Khairuddin; Musril, Hari Antoni; Okra, Riri (Indonesian Research Journal on Education, 2023)
This research is motivated by a phenomenon from the results of the author's observations about the lack of interest in the use of learning media provided by the teacher, where the media used by the teacher is still in the form of handbooks and blackboard media, so students feel bored and not enthusiastic about learning, and have a great impact on student learning outcomes. The method used in this study uses a quantitative approach to the type of quantitative correlation research method. Data collection using observation techniques, questionnaires, and documentation. This research was conducted at SMAN 1 Tigo Nagari. For the population, namely all class X at SMAN 1 Tigo Nagari, totaling 252 people, from this population, the authors took 15% of the population so the total sample was 38 students. The data analysis technique that the author did was a prerequisite analysis test in the form of a data normality test and a linearity test. Then the final data analysis the author uses is correlation analysis. Based on the results of the study it can be seen that the significance level between the interactive learning media variable (X) and student learning outcomes (Y) is tcount = 6.86 with rcount = 0.753, the hypothesis is accepted which states that there is an influence of interactive learning media on student learningoutcomes in the eyes lesson. Information and Communication Technology Guidance lesson, that means H0 is rejected and H1 is accepted. This is evidenced by the value of 0.753 which is at the interval coefficient of 0.60-0.799 so the two variables are included in the strong category.